Una metodologia GIS per la valutazione della suscettibilità da frana - Gabriele, Leoni; Fubelli, Giandomenico; Dramis, Francesco; Mattei, Massimo; Lucifora, Stella; Barchiesi, Fabrizio; Catallo, Fabrizio; Pezzo, Giuseppe; Puglisi, Claudio (GEOmedia, 2010)
GIS methodology to assess landslide susceptibility: application to a river catchment of central Italy This paper illustrates a GIS supported methodology for the assessment of landslide susceptibility. The methodology involves four steps: survey, site analysis, macro-area analysis, and susceptibility analysis. Statiscal and GIS processing of basical large scale geological dataset leads to the recognition of discriminating parameters (land conditions necessary but not sufficient to trigger landslides) and predisposing factors (conditions that worsen slope stability) separately for each landslides types. The susceptibility function combines GIS data to draw landslide susceptibility maps. These results represent the preliminary step for the assessment of landslide hazard and risk.